Pengembangan marketplace wisatakonveksi.com untuk mewujudkan Desa Wonorejo menjadi Desa Wisata konveksi - Fuad Anwar; Mohtar Yunianto; Fendi Aji Purnomo (Adi Widya : Jurnal Pengabdian Masyarakat, 2021)
Wonorejo Village, which is located in the Polokarto District, Sukoharjo Regency, is one of the central villages for convection products, almost 75% of the population is entrepreneurs in the convection business, the decline in turnover has been very significant since the Covid 19 pandemic in mid-2020, the most affected is in the product marketing process. company results. Initial efforts to restore the economy and increase the bargaining power of the Village have been carried out by initiating development into a Convection Tourism Village. The steps that have been taken are to carry out an inventory of convection throughout the village and develop a marketplace, the results obtained are that 80 convection businesses have been recorded and an e-commerce web has been created whose address is wisatakonveksi.com, as a follow-up to this effort is to conduct sales process training and socialize the existence of this marketplace.